Advanced leachate treatment at Buckden landfill, Huntingdon, U.K. Issue 4 (1st July 2003) - Robinson, Howard; Carville, Martin; Walsh, Tim
Abstract : During April 1994, Aspinwall and Company was appointed to design and commission a treatment plant to treat leachate from the Buckden South Landfill Site, located about 1 km SW of Huntingdon in Cambridgeshire, U.K. The landfill is located in the flood plain of the River Great Ouse, which flows within 400 m of the site. Leachate characterization and flow studies took place during early 1994, after an extensive fin drain collection and interception system had been installed. Aspinwall then undertook leachate treatment trials, as part of the detailed design of the on-site treatment plant that needed to be capable of treating 200 m 3 /d of leachate to very high standards. The treatment trials were carried out to investigate and design an aerobic biological process that would provide primary treatment, before secondary effluent polishing stages that would involve reed beds and ozonation. The latter specialized stage was intended to provide treatment of a range of pesticides, including the herbicides mecoprop and isoproturon, which were found in leachate and might not be removed fully by biological treatment stages. The leachate also contained contaminants typical of methanogenic conditions, including ammoniacal-N at values in excess of 400 mg/L, with a required effluent discharge consent standard of 10 mg/L. Key words: leachate, mecoprop, isoproturon, biological treatment, ozonation, reed bed, toxicity-based consent.